THE IMPACT OF URBANIZATION ON LANGUAGE USE IN DEVELOPING COUNTRIES - Qadamova Ruxshona Xabibulla qizi (TADQIQOTLAR.UZ, 2024)
Urbanization has become a significant phenomenon in developing countries, bringing about profound social, economic, and cultural transformations. One of the notable impacts of urbanization is its effect on language use. This article explores how rapid urban growth influences linguistic practices, particularly in the context of multilingual societies in developing nations. Urban centers become melting pots of diverse linguistic communities, resulting in both challenges and opportunities for language maintenance, shift, and evolution.